THE USE OF NEW PEDAGOGICAL TECHNOLOGIES IN UPBRINGING - Abidova Mamurakhon Alisherovna (Western European Studies, 2024)
The article shows the use of modular and contextual learning technologies that ensure the development of engineering thinking of a future specialist in the example of the course "General Chemical Technology" in the preparation of a chemical process engineer.
Keywords: engineer; chemical technologist; educational technology